- Strengthening The Character Of Students Through The Pancasila Student Profile In Madrasah Ibtidaiyah: - - Moch. Farich Alfani Farich; Sholikin Sholikin (PGMI IAIN Lhokseumawe, 2025)
Character is a trait that every student must have. The strengthening of character in each curriculum has been renewed. In the 2013 curriculum it is known as Strengthening Character Education (PPK) which includes eighteen characters that students should have. Strengthening character in the Merdeka Curriculum through the Pancasila Student Profile which has six dimensions, namely: 1) faith, devotion to God Almighty, and noble character, 2) independence, 3) mutual cooperation, 4) global diversity, 5) critical reasoning, 6) and creative. The aim of this research is to describe the strengthening of the character of students in the Madrasah Ibtidaiyah (MI) education unit through the Pancasila Student Profile. Information about strengthening character through P5 is very urgent in shaping the morals or manners of students at the primary school. Apart from that, the independent curriculum which contains P5 (Strengthening Pancasila Student Profile Project) is a new term, so it needs to be studied in depth in the attitude dimension. and its implementation in educational units. The method used in this study is library research by examining journals, scientific articles and other literature as sources of information. The results of this study can strengthen the profile of Pancasila students through intra-curricular, co-curricular and extra-curricular activities. Besides that, it can also be developed through exemplary, habituation, and enforcement of rules in educational units.